2013
DOI: 10.1155/2013/356086
|View full text |Cite
|
Sign up to set email alerts
|

Pure Androgen-Secreting Adrenal Adenoma Associated with Resistant Hypertension

Abstract: Pure androgen-secreting adrenal adenoma is very rare, and its diagnosis remains a clinical challenge. Its association with resistant hypertension is uncommon and not well understood. We present an 18-year-old female with a 10-year history of hirsutism that was accidentally diagnosed with an adrenal mass during the evaluation of a hypertensive crisis. She had a long-standing history of hirsutism, clitorimegaly, deepening of the voice, and primary amenorrhea. She was phenotypically and socially a male. FSH, LH, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
4
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 18 publications
(23 reference statements)
1
4
0
1
Order By: Relevance
“…Rodríguez‐Gutiérrez et al . also reported that an 18‐year‐old woman with an adrenal tumor that produced only androgen presented with hirsutism, amenorrhea, hypertension, and elevated testosterone levels, and surgery on the adrenal tumor led to an improvement in symptoms 5 . Likewise, in the present case, hypertestosteronemia may potentially have been the cause of hypertension and heart failure in the patient.…”
Section: Discussionsupporting
confidence: 63%
“…Rodríguez‐Gutiérrez et al . also reported that an 18‐year‐old woman with an adrenal tumor that produced only androgen presented with hirsutism, amenorrhea, hypertension, and elevated testosterone levels, and surgery on the adrenal tumor led to an improvement in symptoms 5 . Likewise, in the present case, hypertestosteronemia may potentially have been the cause of hypertension and heart failure in the patient.…”
Section: Discussionsupporting
confidence: 63%
“…Similarly, in transgender population studies, testosterone increased blood pressure [ 37 ]. An association of male sex steroids with the reduction of pressure natriuresis has been proposed previously as a contributing cause of hypertension [ 15 ]. In our review of childhood PASACT cases, only one patient had arterial hypertension, which normalized 2 months after surgery [ 15 ].…”
Section: Discussionmentioning
confidence: 99%
“…An association of male sex steroids with the reduction of pressure natriuresis has been proposed previously as a contributing cause of hypertension [ 15 ]. In our review of childhood PASACT cases, only one patient had arterial hypertension, which normalized 2 months after surgery [ 15 ]. In this case, the levels of 11-deoxycorticosterone, a potent mineralocorticoid, were normal.…”
Section: Discussionmentioning
confidence: 99%
“…The increased DHEAS was used as a marker of increased adrenal activity, so the circulating DHEAS level has been used to screen androgen from ovary or adrenal gland [2]. Functional adrenal tumors mainly include those secreting aldosterone or cortisol, and a few secreting both cortisol and androgen, but pure androgen-secreting adrenal tumors (PASATs) are rare, most of which are reported as case studies, and this kind of PASATs that only secrete testosterone with normal adrenal androgens (DHEA, DHEAS and androstenedione) are more rare [3]. Herein, we report a case of benign androgen-secreting adrenal tumor in a postmenopausal elderly woman, with markedly elevated testosterone levels while DHEAS and androstenedione were within normal range.…”
Section: Introductionmentioning
confidence: 99%